Rūznāmah-ʼi safar-i Gīlān - Nāsir al-Dīn Shāh (Mu'assasah-'i Farhangī-i Jahāngīrī, 1988)
Travel impressions of Gilan, Iran, 1869; includes explanatory notes and an introduction (30 p.) by Manūchihr Sutūdah.